2019
DOI: 10.1007/s10763-019-10035-y
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Students in Using Energy Ideas to Interpret Phenomena: The Role of an Energy Representation

Abstract: In the sciences, energy is an important idea to get insight into phenomena, as energy can help to reveal hidden systems and processes. However, students commonly struggle to use energy ideas to interpret and explain phenomena. To support students in using energy ideas to interpret and explain phenomena, a range of different graphical representations are commonly used. However, there is little empirical research regarding whether and how these representations actually support students' ability to use energy ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The energy chain model plays a key role in our teaching sequence, since it facilitates coherence between the phenomenological level and the "theory" level (Tiberghien, 1994;Tiberghien, 1996;Meli & Koliopoulos, 2019) of knowledge, which, in our case, combines technological, scientific and environmental knowledge dimensions. Both contemporary and older scholarship puts the energy chains or other thermodynamic models with a respective graphical representational power forward as proper explanatory energy models, especially for younger students (Tiberghien & Megalakaki, 1995;Papadouris & Constantinou, 2016;Scherr, Harrer, Close, Daane, DeWater, Robertson et al, 2016;Boyer & Givry, 2018;Kubsch, Nordine, Fortus, Krajcik & Neumann, 2019;Delegkos & Koliopoulos, 2020). These models are compatible with linear causal reasoning, common for all learners, regardless of their age (Tiberghien, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The energy chain model plays a key role in our teaching sequence, since it facilitates coherence between the phenomenological level and the "theory" level (Tiberghien, 1994;Tiberghien, 1996;Meli & Koliopoulos, 2019) of knowledge, which, in our case, combines technological, scientific and environmental knowledge dimensions. Both contemporary and older scholarship puts the energy chains or other thermodynamic models with a respective graphical representational power forward as proper explanatory energy models, especially for younger students (Tiberghien & Megalakaki, 1995;Papadouris & Constantinou, 2016;Scherr, Harrer, Close, Daane, DeWater, Robertson et al, 2016;Boyer & Givry, 2018;Kubsch, Nordine, Fortus, Krajcik & Neumann, 2019;Delegkos & Koliopoulos, 2020). These models are compatible with linear causal reasoning, common for all learners, regardless of their age (Tiberghien, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed on teaching energy in school. Researchers are still testing theories and methods to understand better what and how to teach specific energy topics (Bächtold & Munier, 2019 ; Constantinou & Papadouris, 2012 ; DeWaters et al, 2013 ; Kubsch et al, 2020 ). There is a lack of consensus in the literature when considering what exact topics should be introduced at the secondary level.…”
Section: Research Contextmentioning
confidence: 99%
“…Previous studies have indicated that a context and cognitive tools provided, such as graphical representations, can influence students' sensemaking processes (e.g. Ding et al, 2021;Kubsch et al, 2020). In this study, a predicting-observing-explaining (POE) strategy (White & Gunstone, 1992) was employed to guide students to make sense of a scientific phenomenon.…”
Section: Making Sense Of Scientific Phenomenamentioning
confidence: 99%
“…Recently, making sense of phenomena has been of growing interest in the field of science education (e.g. Ding et al, 2021 ; Krajcik, 2015 ; Kubsch et al, 2020 ; National Research Council, 2012 ). The ability to make sense of phenomena is essential for developing scientific understanding and advancing critical thinking.…”
Section: Introductionmentioning
confidence: 99%